Penjanaan perjalanan oleh kawasan industri - Riza Atiq O.K. Rahmat,; Moh. Sofian Asmirza,; Amiruddin Ismail, (1998)
Presently, transport planners use the four-step transport model to forecast future transport demand and scenarios. The first and the most important step in the model is trip generation. Previous transport studies that were carried out in Malaysia did not give enough emphasis on industrial trips. In this particular study the character of each type of industry and its relationship with trip generation were examined. Regression and category analysis procedures were adopted to analyse the trip-making characteristic in order to produce suitable models. Klang Valley area was chosen for this study. A set of statistically sound model for container-trailer trips has been developed for industrial premises which cover a land area of greater than one hectare. In the case of smaller premises, a set of statistically good model for lorries, vans dan factory buses has also been developed